Mapping the Food Allergy Quality of Life Questionnaire Parent Form onto the Short‐Form Six‐Dimensions version 2. Issue 6 (5th December 2021) - Watts, Yan; Dufresne, Élise; Samaan, Kathryn; Graham, François; Labrosse, Roxane; Paradis, Louis; Des Roches, Anne; Poder, Thomas G.; Bégin, Philippe
Abstract: Background: The Food Allergy Quality of Life Questionnaire Parent Form (FAQLQ‐PF) is the most widely used quality of life questionnaire in food allergy. The objective of this study was to develop a mapping algorithm to convert FAQLQ‐PF scores into health state utilities. Methods: The Short‐Form Six‐Dimensions version 2 (SF‐6Dv2) and FAQLQ‐PF questionnaires were collected from an academic center oral immunotherapy referral cohort. Utility estimates were derived from the SF‐6Dv2 using the food allergy preference set. Candidate mapping algorithm models were developed using seven regression methods starting from either the total average score, the average scores of each of the three domains or the individual item scores of FAQLQ‐PF. The process was repeated twice, including only section A, common to all age groups, or including all age‐applicable sections of the FAQLQ‐PF. The mean absolute error (MAE) and root mean squared error (RMSE) were used to select the best fitting model. An independent cohort from a previous national online survey was used for external validation. Results: In the index cohort, 1000 of 1257 respondents had completed both questionnaires. The lowest MAE (0.0791) and RMSE (0.1020) were recorded when entering individual item scores in a categorical regression model. The model including only FAQLQ‐PF section A was found to be most consistent when tested in the external validation cohort ( n = 248) (MAE of 0.0898). Conclusion: The FAQLQ‐PF was mapped onto SF‐6Dv2 utilities with good predictive accuracy in two independent cohorts. This will enable calculation of health utility for cost‐effectiveness analyses in food allergy. Abstract : The FAQLQ‐PF was mapped onto the SF‐6Dv2 using the food allergy value set. The algorithm was validated in an independent cohort as well as in patients undergoing oral immunotherapy. Health utility values can now be derived directly from FAQLQ‐PF questionnaires used in clinical trials.Abbreviations: FAQLQ‐PF, The Food Allergy Quality of Life Questionnaire Parent Form; SG‐6Dv2, The Short‐Form Six‐Dimensions version 2